A simplified standard of the “language” in I. Stalin’s "Marxism and issues in linguistics": from the past to the present and beyond - Andrey Vdovichenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
In a number of newspaper publications by I. Stalin (summer 1950), combined in the form of a separate work “Marxism and problems of linguistics”, the interpretation of the main issues of the theory of the verbal process (“language”) is generally consistent with traditional (including modern quantitatively predominant) linguistic views, among which the main thing is the subject-instrumental perception of "linguistic unity" and attributing to it a semantic function, or the function of meaning formation. This article outlines aspects of criticism of the Stalinist and, in general, linguistic understanding of "language" from the point of view of the communicative model. The Marxist-linguistic consensus emerges from a simplistic view of the word-containing semiotic process. Stalin’s views are presented in the article as an illustration of any vulgarizing approach to sign-containing influence. A simplified (linguistic) model of a word-containing semiotic process is the result of excessive attention to the verbal substrate (“words”), an attempt to present verbal units as self-organized semantic-formal modules responsible for everything that happens in the field of communicative meaning formation. The ineffectiveness of the theoretical verbal construct "language" (and "speech") lies in the imposition of its own action on verbal "bodies", while the generation of meaning in natural word-containing communication is entirely carried out by the complex (polymodal, multichannel) personal influence of the semiotic actor.